ANALYSIS OF THERMAL TRANSFER VALUES IN TEACHING CLASSROOMS - Tri Wulan Sari; Dyah Nurwidyaningrum; Jonathan Saputra; Denny Yatmadi; Sujito Sujito (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2024)
Erratic weather, such as intense heat followed by heavy rain, is causing air pollution in the sky of Jakarta. According to the SNI 03-6389-2011, which deals with energy conservation in building envelopes, the overall thermal transfer value (OTTV) for walls should not exceed 35 W/m2. This study aims to analyze OTTV in Class T and Class S. Class S uses clear glass, while Class T has a shading device in the form of a sunglass sticker. The method used involves calculating the total outer wall area, glass area, window-to-wall ratio (WWR), solar factor value, and then obtaining the OTTV. The results of the study show that the WWR value for Class T was 0.5, while for Class S it was 0.4. The OTTV value in Class T is 58.74 W/m2, whereas the OTTV in Class S is 70.64 W/m2. Despite both classrooms not meeting the SNI requirements, the classrooms using shading devices have OTTV values closer to the SNI standard.